Do Investors Value Higher Financial Reporting Quality, and Can Expanded Audit Reports Unlock This Value? - Elliott, W. Brooke; Fanning, Kirsten; Peecher, Mark E. (The Accounting Review, 2020)
ABSTRACT We present new theory and experimental findings indicating that investors ascribe value to firms that use higher financial reporting quality (FRQ), controlling for the influence of higher FRQ on their estimates of these firms' fundamental value. To guide our investigation, we draw on the cooperation literature in accounting, finance, and psychology. We identify expanded audit reports, particularly auditor commentary, as a mechanism that credibly communicates whether a firm uses higher FRQ. Auditor commentary increases investors' willingness to pay (WTP) more for shares of a firm using higher FRQ than a competing firm using lower FRQ. We also provide process evidence that investors perceive higher FRQ as cooperative behavior by measuring their affective responses and cognitive beliefs, which mediate the influence of audit commentary on investors' increased WTP for higher FRQ. A second experiment bolsters the link between investors' affective and cognitive responses to a firm's FRQ and perceived cooperative behavior.